The Essence of Teaching Dialogic Speech to the Students of Philological Departments - Lysak, Halyna (Pedagogical Discourse, 2015)
The essence of concept «dialogic speech» has been analyzed in the article. Communicative, psychological and language peculiarities of dialogic speech have been determined. Different approaches to the teaching dialogic speech to the students of philological departments have been analyzed. Two main approaches to the teaching dialogic speech have been revealed: the first approach is «downward» – when the students listen to the examples and then compose their own dialogues; the second one is «upward» – students learn some elements of the dialogues and then compose their own dialogues. It has been concluded that teaching dialogic speech is conducted according to the system which includes consistency of studied material, dialogue modeling according to the theme usage of communication situations and the development of students’ creative activity.